Faculty perspectives on facilitating medical students' longitudinal learning: A mixed‐methods study. Issue 10 (14th June 2022) - Shagrin, Bianca S.; Gheihman, Galina; Sullivan, Amy M.; Li, Honghe; Hirsh, David A.
Abstract: Introduction: Medical students' longitudinal care of patients supports clinical learning and promotes patient‐centredness. The literature presents little empirically derived guidance for faculty to facilitate students' longitudinal learning and care. Informed by the conceptual framework of relational learning, this study investigated faculty perspectives about longitudinal teaching, their strategies for facilitating students' longitudinal learning and perceived barriers and enablers. Methods: Using a convergent mixed‐methods approach at a single academic medical centre, the authors conducted a survey and two focus groups in 2018–2019 with faculty members teaching in three longitudinal clinical courses. Quantitative analyses included descriptive statistics and chi‐square tests. Qualitative content analysis described deductive categories and identified inductive themes. Results: Forty‐three eligible faculty (69%) completed the survey. Ninety‐one percent (n = 39) reported that teaching in a longitudinal model enhanced their experience as preceptors. Faculty described activities students performed to provide longitudinal care: spending time with patients independently (n = 38, 88%), making follow‐up phone calls (n = 35; 81%) and participating in home‐ and community‐based visits (n = 20, 47%), among others. Twelve faculty participated in two focus groups. Deductive analysis characterised strategies for facilitating students' longitudinal learning and barriers and enablers. Strategies included "encouraging students to follow patients, " "faculty adaptability, " "offering guidance and setting expectations, " and "careful patient selection." Barriers included scheduling limitations, and enablers included student initiative. Inductive analysis identified two themes: faculty goals for students and faculty benefits from teaching. Goals included meaningful engagement with patients and their illness over time. Benefits from teaching included personal gratification, mentorship, and holistic student assessment. Discussion: Our survey and focus group findings demonstrated positive faculty attitudes and experiences, characterised faculty goals and approaches, and identified elements of the educational context that hindered or facilitated longitudinal teaching and learning. This study's faculty perspectives build upon prior investigations of students' and patients' perspectives, offer teaching strategies, and may guide faculty development. Abstract : This mixed‐methods study identified goals, strategies, barriers and enablers of longitudinal learning and caregiving. Findings are situated within the framework of relational learning and can inform faculty development.